The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.contraception.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum uptake of contraception in rural northern Malawi: A prospective study

Abstract: ObjectivesCross-sectional estimates of contraceptive use do not provide understanding of time to postpartum uptake. This paper uses a range of Malawian data sources: a prospective study to explore time to uptake of contraception and a cross-sectional survey to assess whether sexually active postpartum women whose fecundity has returned use contraception, and whether abstaining/amenorrheic women report using contraception.Study designA demographic surveillance site (DSS) in Malawi was used to identify 7393 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
(20 reference statements)
0
16
1
Order By: Relevance
“…The women included in this analysis had high levels of education and were mostly from urban areas in Lilongwe district, which has been shown to have higher postpartum family planning use than most districts in Malawi[8]. The recently published study by Dasgupta used a rural population in northern Malawi and reported that 28.4% of women using modern methods by 6 months and 45.8% using modern methods by 12 months after delivery[9]. However, these proportions included women who reported abstinence and also using a contraceptive method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The women included in this analysis had high levels of education and were mostly from urban areas in Lilongwe district, which has been shown to have higher postpartum family planning use than most districts in Malawi[8]. The recently published study by Dasgupta used a rural population in northern Malawi and reported that 28.4% of women using modern methods by 6 months and 45.8% using modern methods by 12 months after delivery[9]. However, these proportions included women who reported abstinence and also using a contraceptive method.…”
Section: Discussionmentioning
confidence: 99%
“…In a study that used a minimum of data from three visits in the first 12 months after delivery in a cohort of urban women in Nairobi, 32% of women discontinued their initial contraceptive method by 6 months and 49% by 12 months after initiation[10], similar to our results. Another recent study of rural postpartum women in Malawi found that only 5 of 169 modern contraceptive users reported use of more than one modern method in the year after delivery[9], though the number of encounters per woman (where an opportunity to record method discontinuation would arise) in this study was not specified. Contraceptive switching at other time points (outside of the postpartum period) has been studied, and a review of DHS data from 25 countries (including Malawi) demonstrated an overall method discontinuation (and switching) rate of 38% by 12 months after initiation[15].…”
Section: Discussionmentioning
confidence: 99%
“…Although most women in low‐income countries want to delay or prevent future pregnancies after giving birth (Pasha et al. ; Dasgupta, Zaba, and Crampin ), only 25–34 percent report using any contraception in the 3–12 months postpartum (Keogh et al. ; Rutaremwa et al.…”
mentioning
confidence: 99%
“…They most commonly use relatively short‐acting methods such as injections, which have high discontinuation rates (Keogh et al. ; Dasgupta, Zaba, and Crampin ).…”
mentioning
confidence: 99%
“…For the postpartum women, contraceptive use supports them to limit or delay childbearing depending on their reproductive intentions [14]. However, few postpartum women in sub-Saharan Africa embrace contraception and those using contraceptives often depend on short acting or traditional methods [15,16]. Studies in the region show that some postpartum women misinterpret breastfeeding as a method of contraception even when the criteria for lactation amenorrhea method (LAM) are not met [17,18].…”
Section: Introductionmentioning
confidence: 99%